Title IX Compliance, Clery Act, VAWA, and the Department Chair - Stephen F Pyle; David A Line (Academic Chairpersons Conference Proceedings, 2018)
This interactive research based workshop will review findings regarding expectations of Chairs in facilitating compliance efforts by the University in both traditional and distance learning environments. Chairs will explore through case study analysis how compliance with Title IX, Clery Act, and Violence Against Women Act serves their department.
Keywords: Online; Title IX; VAWA; Clery Act; Compliance